Registry Application Design and Development - sutrisno situmorang (Marqcha Institute, 2023)
Registry is a central database that stores configuration settings on an operating system, in this case a Microsoft Windows. Registry on Windows OS usually contains information and settings for hardware, software and the operating system itself, non-system software. These settings are set by Key. In this study, the author makes a Registry system application which can edit, create and delete the Registry. To design this software, the writing uses the Visual Basic 6.0 programming language due to the convenience provided in the design and manufacture of programs